2015
DOI: 10.1159/000369782
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of Glucose Metabolism Precedes Pressure Overload-Induced Left Ventricular Hypertrophy: Review of a Hypothesis

Abstract: When subjected to pressure overload, the ventricular myocardium shifts from fatty acids to glucose as its main source for energy provision and frequently increases its mass. Here, we review the evidence in support of the concept that metabolic remodeling, measured as an increased myocardial glucose uptake using dynamic positron emission tomography (PET) with the glucose analogue 2-deoxy-2-[18F]fluoro-D-glucose (FDG), precedes the onset of left ventricular hypertrophy (LVH) and heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 47 publications
3
67
0
Order By: Relevance
“…Increasing studies have indicated that a shift away from FAO and back to glucose oxidation occurs partly due to the downregulation of PGC-1α and its coactivated targets, such as PPARs (Huss et al, 2007;Abel et al, 2011). On the other hand, glucose oversupply results in the activation of mTOR pathway (Kundu et al, 2015). In an effort to maintain a delicate balance between energy transformation and utilization, this fuel shift may initially serve as an adaptive transition and play a compensatory role in meeting the energy demands of contraction by adapting metabolic machinery of heart.…”
Section: Fuel Shiftmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing studies have indicated that a shift away from FAO and back to glucose oxidation occurs partly due to the downregulation of PGC-1α and its coactivated targets, such as PPARs (Huss et al, 2007;Abel et al, 2011). On the other hand, glucose oversupply results in the activation of mTOR pathway (Kundu et al, 2015). In an effort to maintain a delicate balance between energy transformation and utilization, this fuel shift may initially serve as an adaptive transition and play a compensatory role in meeting the energy demands of contraction by adapting metabolic machinery of heart.…”
Section: Fuel Shiftmentioning
confidence: 99%
“…In an effort to maintain a delicate balance between energy transformation and utilization, this fuel shift may initially serve as an adaptive transition and play a compensatory role in meeting the energy demands of contraction by adapting metabolic machinery of heart. However, over a long period of time, this metabolic shift may be maladaptive and ultimately lead to energy starvation and cardiac diseases Kundu et al, 2015). Indeed, studies of animal models and humans have shown that high-energy phosphate reserves are reduced in the hypertrophied and failing hearts.…”
Section: Fuel Shiftmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, reduced glucose uptake in type 2 diabetes can further increase the heart's dependence on fatty acids, 19 whereas heart failure with reduced ejected fraction (HFrEF), left ventricular (LV) hypertrophy, and ischemic heart failure are associated with a shift from fatty acid to glucose utilization. 18,20,21 It is thought that this metabolic shift occurs because glucose consumes less oxygen per molecule than fatty acids, making it a more efficient substrate, particularly in oxygen-deprived or stressed conditions. 18,22 Understanding this relative substrate use may be beneficial in assessing pathology and the underlying mechanisms and ultimately determining the best course of treatment.…”
Section: The Omnivorous Heartmentioning
confidence: 99%
“…For example, it is unknown whether insulin resistance contributes to HF risk or is rather a physiological adaptation in response to HF, or in the setting of hyperglycemia, dyslipidemia, and increased circulating free fatty acids, adaptation to prevent adverse myocardial substrate metabolism and myocardial fuel overload. [35][36][37][38][39][40][41] Given the failure of glucose control to improve HF risk, it is also important to note the complex metabolic milieu of T2DM, including dyslipidemia, inflammation, endothelial dysfunction, (Figure 1), and targeting these specific comorbidities may favorably influence HF risk independent of glucose control.…”
Section: Association With Hyperglycemiamentioning
confidence: 99%